Psychological Resilience of Chinese Centenarians and Its Associations With Survival and Health: A Fuzzy Set Analysis. (23rd June 2016) - Gu, Danan; Feng, Qiushi
Abstract: Objectives: To investigate psychological resilience (positive adaptations or effective responses to challenges in daily living) and its associations with survival and health among Chinese centenarians. Method: On the basis of the latest 5 waves (2000, 2002, 2005, 2008, and 2011) of a nationwide longitudinal survey in China with more than 7, 400 centenarians, we constructed 5 resilience types using the grade of membership (fuzzy set) method: high, upper middle, lower middle, low, and unable to answer questions. Results: About 50% of male centenarians and nearly 60% of female centenarians have 0% membership in the high resilience group; only 9% of male centenarians and 6% of female centenarians have 80%–100% probability of membership in the high resilience group. Each additional 10-percentage-point increase in the probability of membership in the high resilience group is associated with 2%–4% lower mortality risk; 36%–55% higher odds of no cognitive impairment, self-rated good health, and self-rated good life satisfaction; and 7%–12% higher odds of no activities of daily living (ADL) disability in male centenarians after adjusting for covariates. Results for female centenarians are similar. High resilience is not significantly associated with short-term health decline. Discussion: Higher psychological resilience is associated with a lower mortality and better health among centenarians.